Nobody Wanted to Play - Hunt, Roderick, 2012; Roderick Hunt, 1986; Alex Brychta, 1986 (UK Oxford reading press, 2012)
In (3z(BNobody Wanted to Play,(3y (Ba story from the Oxford Reading Tree series, Kipper feels left out when his friends are too busy to play with him. He tries to join in with what the others are doing, but they all say they$1 (Bre busy. Feeling sad and lonely, Kipper goes off on his own. Eventually, the others realize they miss him and decide to include him. In the end, everyone plays together happily. The story gently explores feelings of exclusion and friendship, making it relatable for young readers.s
Wilf was upset that nobody wanted to play with him. He went to the park by himself and pretended to play different roles like a spaceman, juggler, cowboy, and more. Eventually more children $1! =s
H3
Developing fluency with high-frequency words. Building confidence in decoding CVC and common tricky words. Understanding simple sentence structures. Beginning to infer characters$1 (Bfeelings and motivationss
Keywords: Supplementary reading material